2019
DOI: 10.3389/fpsyg.2019.02778
|View full text |Cite
|
Sign up to set email alerts
|

Life Crafting as a Way to Find Purpose and Meaning in Life

Abstract: Having a purpose in life is one of the most fundamental human needs. However, for most people, finding their purpose in life is not obvious. Modern life has a way of distracting people from their true goals and many people find it hard to define their purpose in life. Especially at younger ages, people are searching for meaning in life, but this has been found to be unrelated to actually finding meaning. Oftentimes, people experience pressure to have a "perfect" life and show the world how well they are doing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
183
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(188 citation statements)
references
References 178 publications
1
183
0
4
Order By: Relevance
“…As several studies have suggested ways forward from here in terms of the economic impact ( Boone et al, 2020 ; Zetzsche, 2020 ), as well as ways to boost the human immune system in order to prevent people from getting sick ( Nilashi et al, 2020 ; Taghizadeh-Hesary and Akbari, 2020 ). In order to make sure that some of the negative mental health effects are counteracted, this calls for effective evidence-based interventions ( Wilson, 2011 ; Figueroa and Aguilera, 2020 ), that can be made available online and are scalable ( Schippers and Ziegler, 2019 ; de Jong et al, 2020 ). Although tele-health and video consultation can alleviate the immediate problems associated with the lock-down, ( Barsom et al, 2020 ; Zhou et al, 2020 ), there may not be enough staff to effectively treat all people that will need mental health care in the aftermath of the global lockdown ( Figueroa and Aguilera, 2020 ; Torales et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As several studies have suggested ways forward from here in terms of the economic impact ( Boone et al, 2020 ; Zetzsche, 2020 ), as well as ways to boost the human immune system in order to prevent people from getting sick ( Nilashi et al, 2020 ; Taghizadeh-Hesary and Akbari, 2020 ). In order to make sure that some of the negative mental health effects are counteracted, this calls for effective evidence-based interventions ( Wilson, 2011 ; Figueroa and Aguilera, 2020 ), that can be made available online and are scalable ( Schippers and Ziegler, 2019 ; de Jong et al, 2020 ). Although tele-health and video consultation can alleviate the immediate problems associated with the lock-down, ( Barsom et al, 2020 ; Zhou et al, 2020 ), there may not be enough staff to effectively treat all people that will need mental health care in the aftermath of the global lockdown ( Figueroa and Aguilera, 2020 ; Torales et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although tele-health and video consultation can alleviate the immediate problems associated with the lock-down, ( Barsom et al, 2020 ; Zhou et al, 2020 ), there may not be enough staff to effectively treat all people that will need mental health care in the aftermath of the global lockdown ( Figueroa and Aguilera, 2020 ; Torales et al, 2020 ). Next to giving the public more information about effective coping styles ( Ibrahimagić et al, 2020 ), an interesting avenue is to make writing interventions available to the wider public, that have proven to have many (mental) health benefits ( Lepore and Smyth, 2002 ; Schippers et al, 2015 ), as well as performance benefits ( Schippers and Ziegler, 2019 ; de Jong et al, 2020 ; Schippers et al, 2020 ). This type of care could even be delivered by a life crafting chatbot ( Dekker et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations